Finding the 'nudge' in hypernudge. (November 2022) - Mills, Stuart
Abstract: 'Hypernudge' describes a group of phenomena which occur at the intersection of behavioural science and computer science, and law. The term been increasingly used in the latter field, though sparingly in behavioural science. As such, 'hypernudge' remains largely absent from the behavioural science lexicon, inhibiting the field from participating within vital discussions surrounding the use of psychological insights with ubiquitous computing. In this article, I search for the 'nudge' in hypernudge by critiquing the differences between the two concepts from a behavioural science perspective. I 'find the nudge' in hypernudge by conceptualising a hypernudge as a system of nudges which change over time and in response to feedback. In this sense, a hypernudge is not a type of nudge, but an arrangement of nudges. This article then engages in an extensive discussion of the implications on this concept for the hypernudging programme, and for nudging more broadly. Highlights: This article investigates how nudge theory fits into hypernudging. Hypernudges are defined as a system of nudges which change over time and in response to feedback. The welfare impact of hypernudging is discussed via 'three burdens.'.